Reclaiming Hands-on Ultrasound for Radiology With a Simulation-Based Ultrasound Curriculum for Radiology Residents. Issue 3 (September 2020) - Suarez-Weiss, Krista Elise; Yang, Heejae; Beland, Michael D.
Abstract : Abstract: Hands-on ultrasound training is included in the curriculum of many medical specialties and is increasingly incorporated into medical school curricula. Despite published curricula for ultrasound training in these specialties, there remains a dearth of such programs for radiology residency programs. At our institution, there has been a perceived decline in ultrasound scanning comfort and skill in trainees. The purpose of this project was to assess the utility and efficacy of a hands-on simulation-based ultrasound course for radiology residents. First-year radiology residents were enrolled in a 2-week simulation-based course for the instruction of hands-on ultrasound training. With the use of a customizable commercial simulation software platform, residents completed didactic modules, virtual simulations, and phantom scans for a 2-week rotation. A dedicated simulation center with scanning models and computer-based software was provided to all residents. Self-assessments and assignments provided benchmarks of performance. All radiology residents were surveyed at the start of the academic year to assess prior experience and comfort with ultrasound scanning. First-year residents were surveyed a second time upon course completion. Presurvey and postsurvey responses suggest that participation in the 2-week ultrasound scanning course contributed to an improvement in perceived scanning knowledge and comfort for participating residents. Based on our initial experience, the scanning curriculum presented here provides a comprehensive introductory course for first-year radiology residents both for ultrasound anatomy and for scanning technique. Continued education in hands-on ultrasound skills is a crucial factor in maintaining radiology's dominance in the modality.